People with Disabilities and Virtual Learning: Challenges for ICT in the Days of Covid-19 (Docentes 2.0 Journal, 2020)
This article highlights the importance of creating educational environments more accessible to people with disabilities (PWD) within the Sustainable Development Goals (ODS). Meeting these SDGs, especially four (inclusive education) is a challenge in situations of isolation. Likewise, the Convention on the Rights of Persons with Disabilities (2006) recognizes the right to information and communication (including Information and Communication Technologies (ICT)). However, achieving virtual learning in this group emerges as a significant challenge in times of Covid-19. With the closure of schools derived from this pandemic, new learning spaces are generated that require skills, knowledge, and technological means. In this sense, the proposed objective is aimed at assessing the main challenges that virtual learning presents in PWD through ICT in times of pandemic. The methodology used was supported by general methods of scientific knowledge to analyze and synthesize various theoretical conceptions about disability. Content analysis was also applied to deepen the legitimized knowledge around this topic. The results obtained highlight the strategies developed in Cuba for inclusive learning (educational programs for all disabled people). However, inadequacies persist in the adjustment of these spaces due to technological gaps and representations that signify learning in times of Covid-19. It is necessary to introduce a complex sociocultural conception of virtual learning where technological resources are adapted to those individual or collective sociocultural characteristics.
Keywords: Virtual learning; people with disabilities; inclusive education; ICT; Covid-19